Effect of bimodal harmonic structure design on the deformation behaviour and mechanical properties of Co-Cr-Mo alloy - Vajpai S. (2017)
© 2015 Elsevier B.V. In the present work, Co-Cr-Mo alloy compacts with a unique bimodal microstructural design, harmonic structure design, were successfully prepared via a powder metallurgy route consisting of controlled mechanical milling of pre-alloyed powders followed by spark plasma sintering. The harmonic structured Co-Cr-Mo alloy with bimodal grain size distribution exhibited relatively higher strength together with higher ductility as compared to the coarse-grained specimens. The harmonic Co-Cr-Mo alloy exhibited a very complex deformation behavior wherein it was found that the higher strength and the high retained ductility are derived from fine-grained shell and coarse-grained core regions, respectively. Finally, it was observed that the peculiar spatial/topological arrangement of stronger fine-grained and ductile coarse-grained regions in the harmonic structure promotes uniformity of strain distribution, leading to improved mechanical properties by suppressing the localized plastic deformation during straining.